Green Procurement Practices and Supply Chain Management in Private Companies: A Case of Grace Form U Ltd Mbale Branch - Diana Chemutai (Uganda Christian University, 2024)
This research was undertaken to examine green procurement practices and supply chain management in private companies. It was guided by three objectives; to find out the effect of e-procurement on supply chain management of grace form (U) Ltd, to analyze the effect of lean supply on supply chain management of grace form (U) Ltd, to assess the effect of supplier engagement on supply chain management of grace form (U) Ltd. The researcher used a sample size of 36 respondents and used questionnaires and interview guide to collect data and later the data was analyzed using the statistical package for social sciences (SPSS). Results of the first objective showed that e-procurement has a significant effect on supply chain management of grace form (U) Ltd. Supported by the following responses; 66% were positive to the statement that the firm implements e-procurement as a strategy due to increased competitor activity; 44% were positive to the statement that the firm continues to rely on mainly traditional procurement systems even through more advanced technologies are available; 50% were positive to the statement that the firm has faced a number of challenges in implementing E-procurement. Results of the second objective revealed that lean supply has a significant effect on supply chain management of grace form (U) Ltd. Supported by the following responses; 42% of the respondents were positive to the statement that there is supplies of products to the end customer in the most efficient manner possible, 55% of the respondents were positive to the statement that the firm incurs lower inventory costs, it can be observed that 56% were positive to the statement that there is an increase in productivity and flexibility. Results of the third objective showed that supplier engagement has a significant effect on supply chain management of grace form (U) Ltd. 61% forming the majority were positive to the statement that respondents basically focus on creating long term relationships with suppliers, 47% were positive to the statement that respondents simplify the process of working together as much as possible, 59% had a positive response to the statement that respondents understand each vendor and personalize the approach. There is need for superiors to employ inventory management strategies for tracking inventory levels and timing replenishment to combat this waste and reduce costs, so that an ecommerce business has just the right amount of inventory on hand just in time to meet customer demand.